Corelation Stress And Dysmenorrhea In MA Hidayatullah Martapura On 2019 - Yuliawardani, Khoirunnisa (JURNAL KEBIDANAN BESTARI, 2023)
Dysmenorrhea is a reproductive health problem that often occurs in young women due to an imbalance of the hormone progesterone in the blood resulting in pain. One of the causes of dysmenorrhea is psychological factors (stress). Based on preliminary studies conducted on 10 female students at MA Hidayatullah Martapura, showed that the results of a brief interview about dysmenorrhea found that 2 people (20%) had no menstrual pain and 8 (80%) had menstrual pain. As many as 6 out of 10 female students (60%) experience anxiety and stress due to the many tasks given at school. The purpose of this research was to determine the relationship between stress and the incidence of dysmenorrhea in female students at MA Hidayatullah in 2019. This study used an Analytical survey research method with a cross sectional approach. The population was all students in MA Hidayatullah Martapura on 2019, amounting to 150 people with 60 sample. Sampling used Proportional Random Sampling. The research instrument used a questionnaire. Analysis data used Chi-square statistical test with a = 0.05%. The result of this study were obtained found that teenagers 25 people (41.7%) who experienced dysmenorrhea and those 35 people (58.3%) who did not experience dysmenorrhea. Teenagers 34 people (56.7%) who experience mild stress and 26 people (43.3%) moderate tress and there was significant relationship between stress with the incidence of dysmenorrhea ( ρ value 0.00). The conclusion of this study was a correlaition between stress and the incidence of dysmenorrhea in female students at MA Hidayatullah Martapura on 2019.